The Culture Of "Coffee" As A Means Of Social Interaction Of Students Faculty Of Social Sciences And Law, Makassar State University - Ramlie, Muh Syafaat (Pinisi Journal of Social Science, 2023)
This study aims to find out 1) the meaning of “coffee” for students of the Faculty of Social Sciences and Law, Makassar State University and 2) Forms of social interaction in “coffee” activities for students of Faculty of Social Sciences and Law, Makassar State University. This type of research is qualitative research and phenomenological approach. The number of informant is 7 students who are detemined based on pretermined criteria namely: 1) status as a active students, 2) Studying at the Faculty of Social Sciences and Law, 3) Students who routinely do coffee activities at least 2 times a week. Data collection techniques are observation, interview, and documentation. Data validity chect is carried out by member check. Data analysis is data condesation, data presentation, dan conclution.The result showed that: 1) The meaning of “Coffee” for students of the Faculty of Social Sciences and Law, Makassar State University, namely: a) Coffee as a sedative when stressed of feeling depressed, and b) Coffee makes us more open with others. 2) Forms of social interaction in the “coffee” activity of students of the Faculty of Social Sciences and Law, Makassar State University, namely: Cooperation